Penerapan Metode Material Requirement Planning untuk Pengendalian Persediaan Bahan Baku Kedelai pada Pabrik Tahu - Dyah Susanti Hayuningrum; Erni Widajanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to analyze the efficiency of raw material inventory control and the application of the Material Requirement Planning method to control soybean raw material inventory at Mr Heri's Tofu Factory. The type of data used is qualitative data and quantitative data. Data sources in research use secondary data and primary data. Data collection methods used were interviews, observation and documentation. The data analysis technique used is to streamline raw material costs using the Material Requirement Planning (MRP) technique. The research results show that the raw material inventory costs according to company policy of IDR 1,553,712 are not efficient, because the total raw material inventory costs are greater than the LFL method of IDR 240,000, EOQ of IDR 297,914 and POQ of IDR 240,000. Based on this, hypothesis 1 which states that